Gumilev’s Creativity in the Reception of G. Adamovich at the pages of Paris “Zveno” - Ли, Ялинь (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
Adamovich’s reception of creativity has deeply personal character, due to the friendship between them and the desire of critics to debunk the negative criticism about him and to represent the, imagine of  a true poet, who was known by the people from his close entourage. Another feature of critical articles by Adamovich that mentioned the name of Gumilev, can be called the teacher's attitude to poetry as standard, which facilitates understanding of the degree of consideration of the author's talent. This position is due to the proximity of the views of the critic and poet on poetry, on this evidence, literary and critical articles of Adamovich and his other works.